River dolphins and flooded forest: Seasonal habitat use and sexual segregation of botos (Inia geoffrensis) in an extreme cetacean environment - Martin, Anthony Richard; Silva, Vera Maria Ferreira da (Journal of Zoology, 2004)
Habitat use by the boto, or Amazon river dolphin Inia geoffrensis, was investigated in and around the Mamirauá Reserve, Brazil. Largely forested with numerous channels and lakes, Mamirauá comprises a variety of seasonal floodplain habitats known collectively as várzea. The annual cycle of flooding in this region (amplitude 11-15 m) dominates all life. Profound seasonal differences in dolphin density between habitats were consistent with known fish movements, in turn dictated by changes in water level and dissolved oxygen. An exodus of botos from floodplain to river at low water prevents dolphins being trapped in areas that become entirely dry. Densities of botos in floodplain channels were seasonally higher (up to 18 km-2) than reported for any cetacean worldwide. Adults were largely segregated by sex except at low water. Females and calves dominated in chavascal habitat - the areas most remote from rivers, which were preferred by males. Probable causes of this segregation are the energetic requirements of calves and the safety of females and/or calves from male harassment. Some 80% of botos occurring on rivers were within 150 m of the margins. The reliance of adult females and calves on várzea in a region with exceptional dolphin densities demonstrates the importance of floodplain habitats for the boto, and may be the key determinant of this species' distribution.
Keywords: Cetacean; Conservation; Floodplain; Habitat Use; Seasonality; Sex-related Difference; Amazon River; South America; Cetacea; Coryphaenidae; Inia Geoffrensis